2017
DOI: 10.3390/ijns3020006
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Lysosomal Storage Diseases: A Concise Review of the Literature on Screening Methods, Therapeutic Possibilities and Regional Programs

Abstract: Newborn screening for lysosomal storage diseases (LSDs) is increasingly being considered as an option. The development of analytical screening methods, of second-tier methods, and of therapeutic possibilities, are paving the way for routine screening for LSDs in the coming years. Here, we give a brief description of the current status quo, what screening methods are currently available or are in the pipeline, what is the current status of therapeutic possibilities for LSDs, what LSDs are the most obvious candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 55 publications
1
58
0
1
Order By: Relevance
“…2,3 In addition, MPSI was added in 2016 to the recommended universal screening panel in the United States. 2,10 Thus live screening for MPSI is currently being performed in 13 US states. 2,10 The newborn pilot studies that preceded live screening demonstrated that the early-onset, nonattenuated phenotype of MPSI can be identified successfully through NBS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In addition, MPSI was added in 2016 to the recommended universal screening panel in the United States. 2,10 Thus live screening for MPSI is currently being performed in 13 US states. 2,10 The newborn pilot studies that preceded live screening demonstrated that the early-onset, nonattenuated phenotype of MPSI can be identified successfully through NBS.…”
Section: Introductionmentioning
confidence: 99%
“…2,10 Thus live screening for MPSI is currently being performed in 13 US states. 2,10 The newborn pilot studies that preceded live screening demonstrated that the early-onset, nonattenuated phenotype of MPSI can be identified successfully through NBS. The daunting problem of identifying the severe late onset phenotypes must however be noted, which may require genotyping after NBS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent screening studies report that prevalence of FD in males may be as high as 1:3100 39 and 1:8500. 38,43 2.1 | Children from families with known Fabry disease Systematic screening of children with at least one first degree relative with FD is the simplest and fastest way to improve the rate of diagnosis. 42 The estimate of 1:3100 38 included five newborns diagnosed with GLA variants which are not disease-causing (p.E66G, p.A143T-three cases, p.R118C).…”
Section: Diagnosis In Childrenmentioning
confidence: 99%
“…Population-wide newborn screening is not currently implemented in any European country except Italy, while Taiwan and several states in the United States systematically screen newborn children for several lysosomal disorders including FD. 38,43…”
Section: Diagnosis In Childrenmentioning
confidence: 99%
“…However, the enormous cost differential for infrastructure, capital investment, personnel and ongoing maintenance between MS/MS and DMF is difficult to justify unless there is substantial evidence of superior performance by the more expensive platform (MS/MS) [1]. We are alarmed that proponents of MS/MS repeatedly make claims to that effect without relevant supporting evidence [1], [2], [3], [4]. The clinical decision point (high risk for an LSD) is made near the LSD assay's low limit of quantification, where pre-analytical factors, including leukocyte count, pseudodeficiency alleles and sample quality cause low enzyme activity that overlaps the high-risk range [5].…”
mentioning
confidence: 99%